MANAJEMEN STRATEGI PEMBELAJARAN BERDIFERENSIASI DI MADRASAH IBTIDAIYAH SWASTA TUNAS CENDIKIA MEULABOH-ACEH BARAT - Aini Safitri (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
This study aims to investigate a number of activities and fundamental decisions made by the highest management of the school towards differentiated learning that must be applied by all school residents in order to achieve the goals set at MIS Tunas Cendikia, West Aceh Regency.This study uses qualitative research methods. The methodology used in this study includes data collection through in-depth interviews, observations of differentiated learning activities carried out in schools, In addition, researchers also collected several documents in the research area and also looked at news reported by print media and online media related to this study. The results of this study describe a number of activities and decisions of school principals in implementing differentiated learning in schools and provide a better understanding of the concept of understanding and differentiated learning strategies in MIS Tunas Cendikia. In addition, it is able to encourage the birth of a policy model for strengthening the implementation of the independent curriculum in the western end of Aceh Province, especially in MIS Tunas Cendikia, West Aceh Regency.